Realitas Kinerja Dosen, Apa Dampaknya? - Mukminat, Siti Silahul (AKADEMIK: Jurnal Mahasiswa Humanis, 2021)
The substance of education is a good generation, but what do we see now? Yes, the answer is to provide quality education. So the question is, who is responsible? Yes, teacher or lecturer. The common thread has been found, so it is the responsibility of educational institutions to find and foster lecturers. Furthermore, it can be said that the root problem of the current shortage is institutional neglect and incompetence (lecturers). Therefore, this study seeks to obtain data to prove the lack of lecturer performance, so that corrective action can be found. To prove this research, scientific efforts are needed that include qualitative methods, descriptive analysis, and triangulation analysis. The results of the study found details of lecturer performance problems, including 1) Low educational level and functional rank, 2) Lack of collaborative research and publications at reputable national and international levels, 3) Lack of cooperation in service and recognition from reputable institutions at the national level and international.